First in vivo traumatic brain injury imaging via magnetic particle imaging. (5th April 2017) - Orendorff, Ryan; Peck, Austin J; Zheng, Bo; Shirazi, Shawn N; Matthew Ferguson, R; Khandhar, Amit P; Kemp, Scott J; Goodwill, Patrick; Krishnan, Kannan M; Brooks, George A; Kaufer, Daniela; Conolly, Steven
Abstract: Emergency room visits due to traumatic brain injury (TBI) is common, but classifying the severity of the injury remains an open challenge. Some subjective methods such as the Glasgow Coma Scale attempt to classify traumatic brain injuries, as well as some imaging based modalities such as computed tomography and magnetic resonance imaging. However, to date it is still difficult to detect and monitor mild to moderate injuries. In this report, we demonstrate that the magnetic particle imaging (MPI) modality can be applied to imaging TBI events with excellent contrast. MPI can monitor injected iron nanoparticles over long time scales without signal loss, allowing researchers and clinicians to monitor the change in blood pools as the wound heals.